Temperature-dependent DC and small signal performance of InGaAs/InP DHBT. (July 2022) - Yan, Silu; Lu, Hongliang; Qi, Junjun; Cheng, Wei; Zhang, Yuming; Zhang, Yimen
Abstract: Temperature-dependent DC and small-signal analysis have been carried out on 0.7 μm × 15 μm InGaAs/InP double heterojunction bipolar transistors over a temperature range of 25 °C–125 °C by on-wafer S -parameter measurements up to 50 GHz. The thermal behavior of DC and equivalent circuit parameters along with their temperature coefficients were analyzed and reported for the first time using the same InP-based DHBT. Most of the DC parameters show a negative with temperature, for example the temperature coefficients of the V BE, on and V BC, on are −1.4 and −1.48 mV/°C, respectively. And the peak current gain declined from 44.04 to 36.09 with the temperature increased from 25 °C to 125 °C. On the other hand, most of the small-signal parameters show a positive trend with temperature, except for the intrinsic base resistance Rbi, intrinsic base–collector capacitance Cbc, intrinsic base–emitter capacitance Cbe, and common-base current transport factor α0 . The results will provide valuable references and insights for future design optimizations of temperature susceptible circuits.